PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA - Annah Fitri Yani; Eti Arini (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the "Effect of Compensation and Motivation on Employee Performance (Case Study at PT. Enseval Putera Megatrading Bengkulu", both partially and simultaneously. The type of research used is quantitative research. The population in this study amounted to 55 people, using the total side technique, which means that all populations are used as research samples. Based on the t test (Partial) on the Compensation variable, it is known that the calculated t value is > t table (12.387 > 1.675) with a probability of t sig 0.000 < 0.05. On the Motivation variable, it is known that the calculated t value is > t table (15.636 > 1.675) with a probability of t sig 0.000 < 0.05. So it can be concluded that both X variables, namely Compensation and Motivation, partially influence employee performance. Based on the results of the f test, it is known that the calculated f value > f table (129,375 > 2.78) with a probability of f sig 0.000 < 0.05, which indicates that Ho is rejected and Ha is accepted, meaning that Compensation and Motivation together (simultaneously) have a positive effect on the performance variable. The R square value obtained is 83.3%, which means it has a strong influence. This figure shows that employee performance can be explained by Compensation and Motivation by 83.3%. The remaining 16.7% is influenced by other factors that are not examined or explained in this study. Keywords: Compensation, Motivation and Employee Performance